PSYCHODYNAMIC ANALYSIS OF THE FUNCTION OF THE RITUAL IN THE STRUCTURE OF THE NEUROSIS OF OBSESSIVE PERSONALITY STATES - MIKAYELYAN, VLADIMIR; MIKAYELYAN, ERIK (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
Ritual, as a historical phenomenon, is a certain ceremony or service with a certain meaning. Religious rituals are known to contain a therapeutic function. There is nothing in psychotherapy that previously would not exist in religion. Consciously or unconsciously, ritual participants experience a certain therapeutic effect and, at the same time, they ascribe improvement to their condition to supernatural forces. During the ritual ceremony there is a need to find a mystical connection between words, actions and their effects.
Keywords: ritual, therapeutic effect, supernatural forces, therapeutic function, religious rituals